Recent Advances in Nutritional Psychiatry - Grosso, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Mental health disorders represent a major public health issue due to their impact on years lived with disability, and cross-talk with other non-communicable diseases, such as cancer, cardiovascular diseases, and diabetes. Importantly, most of these conditions can be prevented by implementing healthy dietary habits. Consequently, a recently developed field of psychiatry, "nutritional psychiatry", is focused on investigating the relationships among dietary factors, eating habits, and mental disorders in order to form methods for the prevention and treatment of mental disorders.This Special Collection from Nutrients will focus on both observational and molecular studies that investigate the effects of nutrients, foods, and whole dietary patterns on mental health. We invited authors to submit reviews and studies providing evidence of the effects of nutritional factors on cognitive function, depression, sleep patterns, stress, and quality of life.